2001
DOI: 10.1002/cne.1182
|View full text |Cite
|
Sign up to set email alerts
|

As the gut ages: Timetables for aging of innervation vary by organ in the Fischer 344 rat

Abstract: To explore the effects of aging on the vagal innervation of the gastrointestinal (GI) tract, male Fischer 344 rats at 3 and 24 months of age were injected in the left nodose ganglion with 3 microl of either 4% wheat germ agglutinin-horseradish peroxidase (to label sensory endings) or 1% cholera toxin subunit B-horseradish peroxidase (to label motor endings). The stomach and duodenum were prepared as wholemounts and processed with tetramethyl benzidine. In addition, to study age-related changes in the myenteric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
89
0
18

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(119 citation statements)
references
References 74 publications
(86 reference statements)
12
89
0
18
Order By: Relevance
“…It is considered that neuronal loss with age would be accompanied by a rearrangement of the remaining elements; as such, it could not be regarded as a degenerative process, as the remaining ganglionic elements would have greater efficiency (Santer and Baker 1988). Similar results were obtained by other authors (Phillips and Powley 2001); however, they believe that neurodegeneration continues linearly throughout life.…”
Section: Effect Of Ascorbic Acid On Myenteric Neurons Of Ratssupporting
confidence: 63%
See 1 more Smart Citation
“…It is considered that neuronal loss with age would be accompanied by a rearrangement of the remaining elements; as such, it could not be regarded as a degenerative process, as the remaining ganglionic elements would have greater efficiency (Santer and Baker 1988). Similar results were obtained by other authors (Phillips and Powley 2001); however, they believe that neurodegeneration continues linearly throughout life.…”
Section: Effect Of Ascorbic Acid On Myenteric Neurons Of Ratssupporting
confidence: 63%
“…MELLO et al changes in the morphology and density of ENS neurons, influencing GIT functioning (Hansen 2003, Phillips andPowley 2007). Neurodegeneration in the myenteric plexus is a characteristic of ageing observed in rodents (Saffrey and Burnstock 1994, Phillips and Powley 2001, Phillips et al 2003Thrasivoulou 2006), with an approximate reduction of 50% in the neuron population for rats between 3 and 30 months of age (Gabella 1996, Phillips andPowley 2007). However, the life stage in which this loss begins is still questioned.…”
Section: Introductionmentioning
confidence: 99%
“…The presence or absence of aging effects on the innervation and function of the stomach could be critical for the satiation process in older people. At a structural level, the aging stomach is more notable for decreasing levels of sympathetic innervation than for loss of afferent fibers (23,24). Motor responses in the stomach are likely to influence the passage of water through the gut, and consequently age associated sympathetic fiber loss could effect the accurate coding of water volume in the stomach.…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistochemical localization of these substances has been important for the analysis of the neuronal circuitry of the ENS [5,6,40]. It has been reported that the neuronal loss in the gastrointestinal tract of the rat starts in early adulthood and continues in a roughly linear manner over the rodent's lifespan [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%